PENINGKATAN PEMBELAJARAN IPA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Muniwastia, Ice (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The background research is the lack of opportunities to expend their ideas and opinions in groups so that students learn to look less active in learning. The purpose of this research is to improve science learning. The subjects were fourth-grade teachers and students Elementary School 03 Pakan Labuah Bukittinggi. This study used qualitative and quantitative approaches to the type of Classroom Action Research (CAR). The results showed that the learning process by using a type of Jigsaw cooperative learning model to improve learning outcomes of Natural Sciences.   Kata Kunci: pembelajaran IPA; pembelajaran kooperatif; tipe jigsaw